Rasgos del lenguaje coloquial en Apocolocyntosis de Séneca el Joven - Berger, Łukasz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The article reviews fragments of the Senecan satire Apocolocyntosis in search of colloquial style. The analysis of some lexical, syntactic and textual phenomena attempts to highlight some linguistic strategies of the author to stylize the literary texts into an oral-like discourse.
Features of colloquial language in Apocolocyntosis of Seneca the Younger
The aim of the present work is to apply methods of discourse analysis into the study of the colloquial language in the Apocolocyntosis by Seneca the Younger. Using this linguistic approach, an effort will be taken to draft some lexical-semantic, syntactical and textual strategies the author of the satire worked with to approximate ts language to sermo cotidianus. A theoretical framework will be considered first so as to establish criteria for a stylistic analysis of the (conceptually) oral discourse in contrast with the (conceptually) written modalities. As a result the article will take into account the phenomena of emotiveness and subjectivity of the message, concreteness and vividness of the meaning as well as simplification and economy of the linguistic units employed. The main part of the work will deal with exemplification of methods of creating a colloquial feel of Apocolocynosis on the level of vocabulary, syntax and the organization of the discourse. In addition, some remarks will be made regarding psycholinguistic motivation for the particular construction of oral texts. To recapitulate this short overlook of colloquial phenomena the artistic efficiency of the Senecan satire will be emphasized. The polyphony and the vividness of oral registers in his work consequently are to be analyzed as means of a humoristic characterization.
Keywords: Seneca; Apocolocyntosis; satire; colloquial language; orality; literacy; sermo cotidianus